The value of routine histological examination of curettings in all first and second trimester abortions - Stewart, Chantal Juanita Michelle (Department of Obstetrics and Gynaecology, 2018)
A prospective study was carried out to assess whether, in first and second trimester abortions, the clinical diagnosis together with the macroscopic appearance of the curettings was an accurate guide to the correct diagnosis, and whether routine histological examination of all curettings was therefore necessary. The study included 1 464 consecutive patients presenting to the Gynaecology Department at Groote Schuur Hospital, Cape Town with clinically diagnosed abortions during the period 1st February 1988 to 31st December 1988. The correlation between the macroscopic appearance and histological examination compatible with the diagnosis of abortion was found to be 86%. Where the diagnosis was in doubt this correlation was lower. The sensitivity of using the macroscopic appearance as a screening test for the diagnosis of abortion was 96%, with a positive predictive value of 91%. The kappa statistic of agreement between macroscopic appearance and histology was 0,26. The incidence of gestational trophoblastic disease in this series was 0.06%. The diagnosis of ectopic pregnancy was not aided by the use of routine histology.